A densifying agent for improving the grain fineness of tin-plated layer, tin-plated electrolyte prepared using the same, and preparation method
By using the dense agent in tin -plated electrolytes, the existing plating of the existing plating solution is plated with a large amount of grain grains when plating in PCB plate, and the fine grain grains and flatter plastic plastic layers are achieved. Appearance and better welding and welding resistance.
Patent Information
- Application Number
- CN202411128187.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-16
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-08-16
AI Technical Summary
When used in the high-demand tin plating of PCB boards, the existing methylsulfonate tin plating solution has a large grain fineness, which affects solderability and uniform flatness performance.
A dense agent includes a dense layer and a tight agent composition that is covered in the slow -release membrane layer. The whole fluorophytic ethanol polyoxyethylene ether, pH tunner, and deodorization water are composed to improve the fineness of the grain layer of the tinten layer.
By using the dense agent, the fineness of the grains of the tin -plated layer is thinner, and the shape of flat and smooth appearance and uniformity is improved. At the same time, the excellent welding and welding resistance of the tin -plated layer is given. The adhesion of the plating layer.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tin-plating electrolyte, and in particular to a densifying agent for improving the grain fineness of a tin-plating layer, and a tin-plating electrolyte prepared by using the densifying agent and a preparation method. Background Art
[0002] With the deepening of the concept of environmental protection and green development, higher requirements have been placed on the corresponding tin plating solution. The traditional tin plating solution (stannous sulfate system, halogen system, stannous fluoroborate system) has gradually been replaced by the environmentally friendly new methyl sulfonate tin plating technology. Methyl sulfonate tin plating technology has become a hot topic for researchers from all over the world.
[0003] Methanesulfonate tin plating solution is mainly composed of divalent tin main salt + acid + reducing agent + complexing agent + surfactant + antioxidant + brightener. Brightener is adsorbed on the uneven raised part of the electrode surface, so that the plating speed of the raised part is lower than that of the recessed part, and the raised part is slower than the recessed part, thus playing the role of making the electrode surface flat.
[0004] At present, common brighteners in the formula of methanesulfonate tin-plating solution include acrolein, methacrolein, cinnamaldehyde, dihydrobenzaldehyde, benzalkyneacetone, and p-chlorobenzalkyneacetone. However, the above common brighteners have little effect on the grain refinement of the formed tin-plating layer, and the grain fineness of the tin-plating layer is ≥0.8 microns. When the above methanesulfonate tin-plating solution is applied to the tin-plating of PCB boards with high requirements, the grain fineness of the tin-plating formed by the existing methanesulfonate tin-plating solution is relatively large, which affects the overall solderability and uniform flatness. In order to further improve the tin-plating quality of PCB boards, the present invention provides a densifier for improving the grain fineness of the tin-plating layer and a tin-plating electrolyte prepared using the densifier and a preparation method. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a densifying agent for improving the grain fineness of a tin-plating layer, and a tin-plating electrolyte prepared using the densifying agent and a preparation method.
[0006] The densifying agent for improving the grain fineness of the tin-plated layer provided by the present invention is achieved by the following scheme:
[0007] A densifier for improving the grain fineness of a tin-plated layer comprises a sustained-release film layer and a densifier composition coated in the sustained-release film layer, wherein the densifier composition comprises hydroxypropane sulfonic acid pyridinium salt, propargyl alcohol ethoxylate, perfluorohexylethanol polyoxyethylene ether, a pH regulator, and deionized water, wherein the pH regulator is composed of methylsulfonic acid combined with at least one of citric acid, gluconic acid, tartaric acid, and pyrophosphoric acid; the deionized water content is ≥50wt%; and the perfluorohexylethanol polyoxyethylene ether accounts for 2-5% of the total mass of the densifier composition.
[0008] Preferably, the hydroxypropane sulfonic acid pyridinium salt is 1-(2-hydroxy-3-sulfopropyl) pyridinium salt, the propargyl alcohol ethoxylate is hydroxyethyl propargyl ether, and the perfluorohexylethanol polyoxyethylene ether is perfluorohexylethanol polyoxyethylene ether CAPSTONE FS-3100.
[0009] Preferably, the mass ratio of the 1-(2-hydroxy-3-sulfopropyl)pyridine betaine salt, hydroxyethyl propargyl ether, and perfluorohexylethanol polyoxyethylene ether CAPSTONE FS-3100 is (10-25):(5-15):(2-5).
[0010] Preferably, the mass ratio of the 1-(2-hydroxy-3-sulfopropyl)pyridine betaine salt, hydroxyethyl propargyl ether, and perfluorohexylethanol polyoxyethylene ether CAPSTONE FS-3100 is 15:7:3.
[0011] Preferably, the pH adjuster is composed of methanesulfonic acid, gluconic acid, and pyrophosphoric acid in a mass ratio of (40-80):(10-20):(5-10).
[0012] Preferably, the sustained-release film layer is a biaxially stretched PU film or a biaxially stretched PET film; the thickness of the sustained-release film layer is 50-100 microns; the sustained-release film layer is filled with a water-soluble filler, and the particle size of the water-soluble filler is 0.95-1.05 times the thickness of the sustained-release film layer.
[0013] The tin-plated layer prepared by the densifier in the present invention and the tin-plating electrolyte formula provided by the present invention has finer grains, which can improve the flatness, smoothness and uniformity of the tin-plated layer, and at the same time can give the tin-plated layer excellent solderability and solder resistance. The tin-plating process is stable, thereby achieving the stability of the tin-plating electrolyte, thereby improving the overall adhesion of the tin-plated layer.
[0014] The densifier composition is composed of 14-16wt% of hydroxypropane sulfonic acid pyridinium salt, 5-8wt% of propynyl alcohol ethoxylate, 3-4wt% of perfluorohexylethanol polyoxyethylene ether, 14-16wt% of pH value regulator, and the balance is deionized water.
[0015] By optimizing the formula of the densifier composition, the grain fineness, morphological smoothness, uniformity, solderability and solder resistance of the tin-plated layer can be improved, while the overall production cost of the densifier can be reduced, thereby reducing the overall tin-plating process cost.
[0016] The present invention provides a tin-plating electrolyte prepared by a densifier for improving the grain fineness of a tin-plating layer, which is achieved by the following technical scheme: the tin-plating electrolyte comprises: 35-40 g / L of stannous methanesulfonate, 75-80 g / L of methanesulfonic acid, 25-30 g / L of citric acid, 100-120 g / L of thiourea, 60-80 g / L of sodium hypophosphite, 5-10 g / L of 2-methyl-2,3-dihydrobenzaldehyde, 1-5 g of phthalimide, 5-10 g / L of alkylphenol polyoxyethylene ether OP-10, 2-5 g / L of PEG 300, 4-6 g / L of catechol, 4-6 g / L of hydroquinone, and 3-8 g / L of a densifier for improving the grain fineness of a tin-plating layer.
[0017] The tin-plating electrolyte provided by the present invention can give the tin-plating layer better grain fineness, smooth and even morphology, uniformity, weldability grooves, and soldering resistance. When used in combination with a densifier for improving the grain fineness of the tin-plating layer, the grain fineness of the tin-plating layer can be further refined and adjusted, and the smooth and even morphology, uniformity, weldability grooves, and soldering resistance of the tin-plating layer can be further improved.
[0018] Preferably, the pH value of the tin-plating electrolyte is 0.6-0.7; the electroplating parameters of the tin-plating electrolyte are as follows: the temperature of the environmentally friendly acidic tin-plating electrolyte is 45-50°C, and the current density is controlled to be 3-5A / dm 2 , the electroplating time is 3-6min.
[0019] By adopting the above technical solution, the grain fineness of the tin-plated layer can be further refined and adjusted, and the morphology flatness, smoothness, uniformity, solderability and solder resistance of the tin-plated layer can be further improved.
[0020] A method for preparing a tin-plating electrolyte prepared by using a densifying agent for improving the grain fineness of a tin-plating layer comprises the following steps:
[0021] S1, preparation of a densifier for improving the grain fineness of the tin-plated layer;
[0022] S1.1, 100 parts of PU resin or PET resin and 5-10 parts of inorganic filler with a water-soluble film attached to the surface are uniformly mixed, melt-extruded, cast, and biaxially stretched to obtain a sustained-release film layer with a thickness of 50-100 μm;
[0023] S1.2, uniformly mixing accurately measured hydroxypropane sulfonic acid pyridinium salt, propargyl alcohol ethoxylate, perfluorohexylethanol polyoxyethylene ether, pH regulator, and deionized water to obtain a densifier composition;
[0024] S1.3, using a laundry beads automatic packaging machine to coat the densifier composition prepared in S1.2 in the slow-release film layer in S1.1, so as to obtain a densifier with a particle size of 4-12 mm for improving the grain fineness of the tin-plated layer;
[0025] S2, firstly, 100 parts of deionized water and 0.4-0.8 parts of triethylenetetraaminehexaacetic acid are mixed evenly and then placed in a reactor for boiling treatment for 5-15 minutes, and after boiling, the air in the reactor is replaced by nitrogen. After the boiling treatment is completed, the temperature is lowered to 0-20° C. and filtered to obtain a deionized water solvent;
[0026] S3, put accurately measured stannous methanesulfonate, methanesulfonic acid, citric acid, thiourea, sodium hypophosphite, 2-methyl-2,3-dihydrobenzaldehyde, phthalimide, alkylphenol polyoxyethylene ether OP-10, PEG 300, catechol, hydroquinone, and the densifier used to improve the grain fineness of the tin plating layer in S1 into a reactor and stir them evenly with the impurity-removed water solvent obtained in S2, then add methanesulfonic acid dropwise to adjust the pH value of the system to 0.6-0.7, and a finished tin plating electrolyte can be obtained.
[0027] The preparation method of the densifier for improving the grain fineness of the tin-plated layer in the present invention is relatively simple, and industrial production can be realized, thereby facilitating the preparation of the tin-plating electrolyte and the implementation of the tin-plating process, thereby reducing the overall tin-plating production cost.
[0028] In summary, the present invention has the following advantages:
[0029] 1. The tin-plated layer prepared by the densifier in the present invention and the tin-plating electrolyte formula provided by the present invention has finer grains, which can improve the flatness, smoothness and uniformity of the tin-plated layer, and at the same time can give the tin-plated layer excellent solderability and solder resistance. The tin-plating process is stable, thereby achieving the stability of the tin-plating electrolyte, thereby improving the overall adhesion of the tin-plated layer.
[0030] 2. The tin-plating electrolyte provided by the present invention can give the tin-plating layer better grain fineness, smooth morphology, uniformity, weldability grooves, and soldering resistance. When used in combination with a densifier for improving the grain fineness of the tin-plating layer, the grain fineness of the tin-plating layer can be further refined and adjusted, and the smooth morphology, uniformity, weldability grooves, and soldering resistance of the tin-plating layer can be further improved.
[0031] 3. The present invention optimizes the electroplating parameters of the tin-plating electrolyte. When the temperature of the environmentally friendly acidic tin-plating electrolyte is 45-50°C and the current density is controlled to be 3-5A / dm 2 The tin-plated layer obtained with an electroplating time of 3-6 minutes has finer grain fineness, smoother morphology, better uniformity, solderability and solder resistance.
[0032] 4. The tin-plating electrolyte in the present invention is relatively simple, which enables industrial production and is also convenient for quality control. DETAILED DESCRIPTION
[0033] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples and comparative examples.
[0034] Example
[0035] A densifier for improving the grain fineness of a tin-plated layer comprises a slow-release film layer and a densifier composition coated in the slow-release film layer, wherein the densifier composition comprises hydroxypropane sulfonic acid pyridinium salt, propynyl alcohol ethoxylate, perfluorohexylethanol polyoxyethylene ether, a pH value regulator, and deionized water.
[0036] The sustained-release film layer is a biaxially stretched PU film or a biaxially stretched PET film. The thickness of the sustained-release film layer is 50-100 microns. The sustained-release film layer is filled with a water-soluble filler. The particle size of the water-soluble filler is 0.95-1.05 times the thickness of the sustained-release film layer.
[0037] The preparation method of the sustained-release film layer is as follows: 100 parts of PU resin or PET resin are uniformly mixed with 5-10 parts of inorganic filler with a water-soluble film attached to the surface, and the mixture is melt-extruded, cast, and biaxially stretched to obtain a sustained-release film layer with a thickness of 50-100 microns.
[0038] Specifically, the hydroxypropane sulfonic acid pyridinium salt is 1-(2-hydroxy-3-sulfopropyl)pyridinium salt. The propargyl alcohol ethoxylate is hydroxyethyl propargyl ether. The perfluorohexylethanol polyoxyethylene ether is perfluorohexylethanol polyoxyethylene ether CAPSTONE FS-3100.
[0039] The pH adjuster is composed of methanesulfonic acid and at least one of citric acid, gluconic acid, tartaric acid and pyrophosphoric acid. Preferably, the pH adjuster is composed of methanesulfonic acid, gluconic acid and pyrophosphoric acid in a mass ratio of (40-80):(10-20):(5-10).
[0040] The content of deionized water in the densifier composition is ≥50wt%. The perfluorohexylethanol polyoxyethylene ether in the densifier composition accounts for 2-5% of the total mass of the densifier composition. Preferably, the mass ratio of -(2-hydroxy-3-sulfopropyl)pyridine betaine salt, hydroxyethyl propargyl ether, and perfluorohexylethanol polyoxyethylene ether CAPSTONE FS-3100 is (10-25):(5-15):(2-5). In the industrial grade formula: the mass ratio of 1-(2-hydroxy-3-sulfopropyl)pyridine betaine salt, hydroxyethyl propargyl ether, and perfluorohexylethanol polyoxyethylene ether CAPSTONE FS-3100 is 15:7:3.
[0041] Preferably, the densifier composition consists of 14-16 wt % of hydroxypropane sulfonic acid pyridinium salt, 5-8 wt % of propynyl alcohol ethoxylate, 3-4 wt % of perfluorohexylethanol polyoxyethylene ether, 14-16 wt % of pH regulator, and the balance is deionized water.
[0042] The preparation method of the densifier used to improve the grain fineness of the tin-plated layer is as follows:
[0043] S1, 100 parts of PU resin or PET resin and 5-10 parts of inorganic filler with a water-soluble film attached to the surface are uniformly mixed, melt-extruded, cast, and biaxially stretched to obtain a sustained-release film layer with a thickness of 50-100 microns;
[0044] S2, uniformly mixing accurately measured hydroxypropane sulfonic acid pyridinium salt, propargyl alcohol ethoxylate, perfluorohexylethanol polyoxyethylene ether, pH value regulator, and deionized water to obtain a densifier composition;
[0045] S3, using a laundry beads automatic packaging machine to coat the densifier composition prepared in S2 in the sustained-release film layer in S1, so as to obtain a densifier with a particle size of 4-12 mm for improving the grain fineness of the tin-plated layer.
[0046] A tin-plating electrolyte prepared by using a densifier for improving the grain fineness of a tin-plating layer comprises: 35-40 g / L of stannous methanesulfonate, 75-80 g / L of methanesulfonic acid, 25-30 g / L of citric acid, 100-120 g / L of thiourea, 60-80 g / L of sodium hypophosphite, 5-10 g / L of 2-methyl-2,3-dihydrobenzaldehyde, 1-5 g of phthalimide, 5-10 g / L of alkylphenol polyoxyethylene ether OP-10, 2-5 g / L of PEG 300, 4-6 g / L of catechol, 4-6 g / L of hydroquinone, and 3-8 g / L of a densifier for improving the grain fineness of a tin-plating layer. The pH value of the tin-plating electrolyte is 0.6-0.7.
[0047] A method for preparing a tin-plating electrolyte prepared by using a densifying agent for improving the grain fineness of a tin-plating layer is as follows:
[0048] S1, preparation of a densifier for improving the grain fineness of the tin-plated layer;
[0049] S2, firstly, 100 parts of deionized water and 0.4-0.8 parts of triethylenetetraaminehexaacetic acid are mixed evenly and then placed in a reactor for boiling treatment for 5-15 minutes, and after boiling, the air in the reactor is replaced by nitrogen. After the boiling treatment is completed, the temperature is lowered to 0-20° C. and filtered to obtain a deionized water solvent;
[0050] S3, put accurately measured stannous methanesulfonate, methanesulfonic acid, citric acid, thiourea, sodium hypophosphite, 2-methyl-2,3-dihydrobenzaldehyde, phthalimide, alkylphenol polyoxyethylene ether OP-10, PEG 300, catechol, hydroquinone, and the densifier used to improve the grain fineness of the tin plating layer in S1 into a reactor and stir them evenly with the impurity-removed water solvent obtained in S2, then add methanesulfonic acid dropwise to adjust the pH value of the system to 0.6-0.7, and a finished tin plating electrolyte can be obtained.
[0051] In order to optimize the performance of the tin-plating layer, the electroplating parameters of the tin-plating electrolyte are as follows: the temperature of the environmentally friendly acidic tin-plating electrolyte is 45-50°C, and the current density is controlled at 3-5A / dm 2 The electroplating time is 3-6 minutes, and the grain fineness of the obtained tin-plated layer is less than 0.8 microns.
[0052] Example 1: A densifier for improving the grain fineness of a tin-plated layer is composed of 15wt% of 1-(2-hydroxy-3-sulfopropyl)pyridine betaine salt, 7wt% of hydroxyethyl propargyl ether, 3wt% of perfluorohexylethanol polyoxyethylene ether CAPSTONE FS-3100, 15wt% of a pH regulator, and the remainder is deionized water. The pH regulator is composed of methanesulfonic acid, gluconic acid, and pyrophosphoric acid in a mass ratio of 7:2:1.
[0053] Preparation method of sustained-release film layer: 100 parts of PET resin and 10 parts of calcium carbonate filler with a particle size of 270-300 mesh and a water-soluble film attached to the surface are mixed evenly, melt extruded, cast, and biaxially stretched to obtain a sustained-release film layer with a thickness of 50 microns. Preparation method of calcium carbonate filler with a particle size of 270-300 mesh and a water-soluble film attached to the surface: 5g of water-soluble resin (Japan Kuraray PVA-205) and 20g of 270-300 mesh calcium carbonate filler are dispersed and mixed evenly at high speed, and dried to obtain.
[0054] The preparation method of the densifier used to improve the grain fineness of the tin-plated layer is as follows:
[0055] S1, 5g of water-soluble resin (Japan Kuraray PVA-205) and 20g of 270-300 mesh calcium carbonate filler are dispersed and mixed uniformly at high speed, and dried to obtain a calcium carbonate filler with a particle size of 270-300 mesh and a water-soluble film attached to the surface; 100 parts of PET resin and 10 parts of calcium carbonate filler with a particle size of 270-300 mesh and a water-soluble film attached to the surface are mixed uniformly, melt-extruded, cast, and biaxially stretched to obtain a sustained-release film layer with a thickness of 50 microns;
[0056] S2, uniformly mixing accurately measured amounts of 1-(2-hydroxy-3-sulfopropyl)pyridine betaine salt, hydroxyethyl propargyl ether, perfluorohexylethanol polyoxyethylene ether CAPSTONE FS-3100, a pH value regulator, and deionized water to obtain a densifier composition;
[0057] S3, using a laundry beads automatic packaging machine to coat the densifier composition prepared in S2 in the sustained-release film layer in S1, so as to obtain a densifier with a particle size of 4-6 mm for improving the grain fineness of the tin-plated layer.
[0058] The tin plating electrolyte formula is as follows: 48g / L stannous methanesulfonate, 80g / L methanesulfonic acid, 25g / L citric acid, 120g / L thiourea, 65g / L sodium hypophosphite, 8g / L 2-methyl-2,3-dihydrobenzaldehyde, 4g phthalimide, 6g / L alkylphenol polyoxyethylene ether OP-10, 4g / L PEG 300, 5g / L catechol, 5g / L hydroquinone, and 3g / L of the above-prepared densifier for improving the grain fineness of the tin plating layer.
[0059] A tin-plating electrolyte prepared by using a densifying agent for improving the grain fineness of a tin-plating layer comprises the following steps:
[0060] S1, preparation of a densifier for improving the grain fineness of the tin-plated layer;
[0061] S2, firstly, 100 parts of deionized water and 0.5 parts of triethylenetetraaminehexaacetic acid are mixed evenly and then placed in a reactor for boiling treatment for 8 minutes, and after boiling, the air in the reactor is replaced by nitrogen. After the boiling treatment is completed, the temperature is lowered to 20° C. and filtered to obtain a deionized water solvent;
[0062] S3, accurately measured stannous methanesulfonate, methanesulfonic acid, citric acid, thiourea, sodium hypophosphite, 2-methyl-2,3-dihydrobenzaldehyde, phthalimide, alkylphenol polyoxyethylene ether OP-10, PEG 300, catechol, hydroquinone, and the densifier used in step 1 for improving the grain fineness of the tin-plated layer are put into a reaction kettle and stirred evenly with the impurity-removed water solvent obtained in step 2, and then methanesulfonic acid is added dropwise to adjust the pH value of the system to 0.6, so as to obtain a finished tin-plating electrolyte.
[0063] The electroplating parameters of the tinning electrolyte are as follows: the temperature of the environmentally friendly acidic tinning electrolyte is 50°C, and the current density is controlled at 3A / dm 2 , the electroplating time is 3min.
[0064] The difference between Example 2 and Example 1 is that a densifier for improving the grain fineness of the tin plating layer is composed of 10wt% of 1-(2-hydroxy-3-sulfopropyl)pyridine amine salt, 5wt% of hydroxyethyl propargyl ether, 2wt% of perfluorohexylethanol polyoxyethylene ether CAPSTONE FS-3100, 12wt% of a pH regulator, and the balance is deionized water.
[0065] The difference between Example 3 and Example 1 is that a densifier for improving the grain fineness of the tin plating layer is composed of 20 wt% of 1-(2-hydroxy-3-sulfopropyl)pyridine amine salt, 10 wt% of hydroxyethyl propargyl ether, 4 wt% of perfluorohexylethanol polyoxyethylene ether CAPSTONE FS-3100, 15 wt% of a pH regulator, and the remainder is deionized water.
[0066] The difference between Example 4 and Example 1 is that a densifier for improving the grain fineness of the tin plating layer is composed of 25wt% of 1-(2-hydroxy-3-sulfopropyl)pyridine amine salt, 15wt% of hydroxyethyl propargyl ether, 5wt% of perfluorohexylethanol polyoxyethylene ether CAPSTONE FS-3100, 16wt% of pH regulator, and the balance is deionized water.
[0067] The difference between Example 5 and Example 1 is that the tin plating electrolyte formula is as follows: 48 g / L stannous methanesulfonate, 80 g / L methanesulfonic acid, 25 g / L citric acid, 120 g / L thiourea, 65 g / L sodium hypophosphite, 8 g / L 2-methyl-2,3-dihydrobenzaldehyde, 4 g phthalimide, 6 g / L alkylphenol polyoxyethylene ether OP-10, 4 g / L PEG 300, 5 g / L catechol, 5 g / L hydroquinone, and 5 g / L of the above-prepared densifier for improving the grain fineness of the tin plating layer.
[0068] The difference between Example 6 and Example 1 is that the tin plating electrolyte formula is as follows: 48 g / L stannous methanesulfonate, 80 g / L methanesulfonic acid, 25 g / L citric acid, 120 g / L thiourea, 65 g / L sodium hypophosphite, 8 g / L 2-methyl-2,3-dihydrobenzaldehyde, 4 g phthalimide, 6 g / L alkylphenol polyoxyethylene ether OP-10, 4 g / L PEG 300, 5 g / L catechol, 5 g / L hydroquinone, and 8 g / L of the above-prepared densifier for improving the grain fineness of the tin plating layer.
[0069] The difference between Example 7 and Example 1 is that the pH adjuster is composed of methanesulfonic acid and pyrophosphoric acid in a mass ratio of 9:1.
[0070] The difference between Example 8 and Example 1 is that the pH adjuster is composed of methanesulfonic acid and gluconic acid in a mass ratio of 8:1.
[0071] The difference between Example 9 and Example 1 is that the pH adjuster is composed of methanesulfonic acid, gluconic acid and pyrophosphoric acid in a mass ratio of 40:10:5.
[0072] The difference between Example 10 and Example 1 is that the pH adjuster is composed of methanesulfonic acid, gluconic acid and pyrophosphoric acid in a mass ratio of 80:10:10.
[0073] The difference between Example 11 and Example 1 is that the electroplating parameters of the tin-plating electrolyte are as follows: the temperature of the environmentally friendly acidic tin-plating electrolyte is 45°C, and the current density is controlled to be 3A / dm 2 , the electroplating time is 3min.
[0074] The difference between Example 12 and Example 1 is that the electroplating parameters of the tin-plating electrolyte are as follows: the temperature of the environmentally friendly acidic tin-plating electrolyte is 50°C, and the current density is controlled to be 4A / dm 2 , the electroplating time is 3min.
[0075] The difference between Example 13 and Example 1 is that the electroplating parameters of the tin-plating electrolyte are as follows: the temperature of the environmentally friendly acidic tin-plating electrolyte is 50°C, and the current density is controlled to be 5A / dm 2 , the electroplating time is 3min.
[0076] The difference between Example 14 and Example 1 is that the electroplating parameters of the tin-plating electrolyte are as follows: the temperature of the environmentally friendly acidic tin-plating electrolyte is 50°C, and the current density is controlled to be 3A / dm 2 , the electroplating time is 4min.
[0077] The difference between Example 15 and Example 1 is that the electroplating parameters of the tin-plating electrolyte are as follows: the temperature of the environmentally friendly acidic tin-plating electrolyte is 50°C, and the current density is controlled to be 3A / dm 2 , the electroplating time is 5min.
[0078] The difference between Example 16 and Example 1 is that the electroplating parameters of the tin-plating electrolyte are as follows: the temperature of the environmentally friendly acidic tin-plating electrolyte is 50°C, and the current density is controlled to be 3A / dm 2 , the electroplating time is 6min.
[0079] The difference between Example 17 and Example 1 is that the electroplating parameters of the tin-plating electrolyte are as follows: the temperature of the environmentally friendly acidic tin-plating electrolyte is 45°C, and the current density is controlled to be 4A / dm 2 , the electroplating time is 5min.
[0080] The difference between Example 18 and Example 1 is that the tin plating electrolyte formula is as follows: 48g / L stannous methanesulfonate, 80g / L methanesulfonic acid, 25g / L citric acid, 120g / L thiourea, 65g / L sodium hypophosphite, 8g / L 2-methyl-2,3-dihydrobenzaldehyde, 4g phthalimide, 6g / L alkylphenol polyoxyethylene ether OP-10, 4g / L PEG 300, 5g / L catechol, 5g / L hydroquinone, 5g / L of the above-prepared densifier for improving the grain fineness of the tin plating layer. The electroplating parameters of the tin plating electrolyte are as follows: the temperature of the environmentally friendly acidic tin plating electrolyte is 50°C, and the current density is controlled to 3A / dm 2 , the electroplating time is 4min.
[0081] The difference between Comparative Example 1 and Example 1 is that a densifier for improving the grain fineness of the tin-plated layer is composed of 15wt% of 1-(2-hydroxy-3-sulfopropyl)pyridine amine salt, 7wt% of hydroxyethyl propargyl ether, and the balance is deionized water.
[0082] The difference between Comparative Example 2 and Example 1 is that a densifier for improving the grain fineness of the tin-plated layer is composed of 15wt% of 1-(2-hydroxy-3-sulfopropyl)pyridine amine salt, 7wt% of hydroxyethyl propargyl ether, 15wt% of pH regulator, and the balance is deionized water.
[0083] The difference between Comparative Example 3 and Example 1 is that a densifier for improving the grain fineness of the tin plating layer is composed of 15wt% of 1-(2-hydroxy-3-sulfopropyl)pyridine amine salt, 7wt% of hydroxyethyl propargyl ether, 3wt% of perfluorohexylethanol polyoxyethylene ether CAPSTONE FS-3100, and the balance is deionized water.
[0084] The difference between Comparative Example 4 and Example 1 is that the pH regulator is methanesulfonic acid.
[0085] The difference between Comparative Example 5 and Example 1 is that the pH regulator is gluconic acid.
[0086] The difference between Comparative Example 6 and Example 1 is that a densifier for improving the grain fineness of the tin plating layer is composed of 15wt% of 1-(2-hydroxy-3-sulfopropyl)pyridine amine salt, 7wt% of hydroxyethyl propargyl ether, 1wt% of perfluorohexylethanol polyoxyethylene ether CAPSTONE FS-3100, 15wt% of pH regulator, and the balance is deionized water.
[0087] The difference between Comparative Example 7 and Example 1 is that a densifier for improving the grain fineness of the tin plating layer is composed of 15wt% of 1-(2-hydroxy-3-sulfopropyl)pyridine amine salt, 7wt% of hydroxyethyl propargyl ether, 6wt% of perfluorohexylethanol polyoxyethylene ether CAPSTONE FS-3100, 15wt% of a pH regulator, and the balance is deionized water.
[0088] The difference between Comparative Example 8 and Example 1 is that the tin plating electrolyte formula is as follows: 48 g / L stannous methanesulfonate, 80 g / L methanesulfonic acid, 25 g / L citric acid, 120 g / L thiourea, 65 g / L sodium hypophosphite, 8 g / L 2-methyl-2,3-dihydrobenzaldehyde, 4 g phthalimide, 6 g / L alkylphenol polyoxyethylene ether OP-10, 4 g / L PEG 300, 5 g / L catechol, 5 g / L hydroquinone, and 1 g / L of the above-prepared densifier for improving the grain fineness of the tin plating layer.
[0089] The difference between Comparative Example 9 and Example 1 is that the tin plating electrolyte formula is as follows: 48 g / L stannous methanesulfonate, 80 g / L methanesulfonic acid, 25 g / L citric acid, 120 g / L thiourea, 65 g / L sodium hypophosphite, 8 g / L 2-methyl-2,3-dihydrobenzaldehyde, 4 g phthalimide, 6 g / L alkylphenol polyoxyethylene ether OP-10, 4 g / L PEG 300, 5 g / L catechol, 5 g / L hydroquinone, and 10 g / L of the above-prepared densifier for improving the grain fineness of the tin plating layer.
[0090] The difference between Comparative Example 10 and Example 1 is that the electroplating parameters of the tin-plating electrolyte are as follows: the temperature of the environmentally friendly acidic tin-plating electrolyte is 40°C, and the current density is controlled to be 3A / dm 2 , the electroplating time is 3min.
[0091] The difference between Comparative Example 11 and Example 1 is that the electroplating parameters of the tin-plating electrolyte are as follows: the temperature of the environmentally friendly acidic tin-plating electrolyte is 55°C, and the current density is controlled to be 3A / dm 2 , the electroplating time is 3min.
[0092] The difference between Comparative Example 12 and Example 1 is that the electroplating parameters of the tin-plating electrolyte are as follows: the temperature of the environmentally friendly acidic tin-plating electrolyte is 50°C, and the current density is controlled to be 1A / dm 2 , the electroplating time is 3min.
[0093] The difference between Comparative Example 13 and Example 1 is that the electroplating parameters of the tin-plating electrolyte are as follows: the temperature of the environmentally friendly acidic tin-plating electrolyte is 50°C, and the current density is controlled to be 2A / dm 2 , the electroplating time is 3min.
[0094] The difference between Comparative Example 14 and Example 1 is that the electroplating parameters of the tin-plating electrolyte are as follows: the temperature of the environmentally friendly acidic tin-plating electrolyte is 50°C, and the current density is controlled to be 6A / dm 2 , the electroplating time is 3min.
[0095] The difference between Comparative Example 15 and Example 1 is that the electroplating parameters of the tin-plating electrolyte are as follows: the temperature of the environmentally friendly acidic tin-plating electrolyte is 50°C, and the current density is controlled to be 3A / dm 2 , the electroplating time is 2min.
[0096] The difference between Comparative Example 16 and Example 1 is that the electroplating parameters of the tin-plating electrolyte are as follows: the temperature of the environmentally friendly acidic tin-plating electrolyte is 50°C, and the current density is controlled to be 3A / dm 2 , the electroplating time is 8min.
[0097] Performance test: 1. Determination of electroplating rate of plating solution: The workpiece to be plated is a copper sheet (30mm×15mm×1.5 mm) that has been surface treated. The current efficiency and deposition rate of electroplated tin in the tin electroplating solution are determined by weighing method. The pre-treated test piece is blown dry and weighed (m1). After electroplating tin for a certain period of time, it is washed and blown dry, and weighed again (m2). Deposition rate v=100(m2-m1) / ρSt, v is the deposition rate (μm / min); m1 is the mass of the unplated sample (g); m2 is the mass of the electroplated sample (g); ρ is the density of tin (7.28g / cm); S is the coating area; t is the electroplating time (min). Current efficiency ηk=[60(m2-m1)]*100% / 2.214It, ηk is the current efficiency%, m1 is the mass of the unplated sample (g); m2 is the mass of the sample after plating (g); I is the current (A); t is the plating time (min); 2.214 is the electrochemical equivalent of divalent tin [g·(A·h)]. 2. Plating grain size: The average grain size of the grains is counted by scanning electron microscopy. 3. Welding hole area: After the resistor is electroplated with tin, a soldering experiment is carried out to measure the percentage of the welding hole area to the total area. 4. Solder resistance: The tinned copper sheet is immersed in the flux, and then immersed in the molten tin at a temperature of 250℃ for 5s. After taking it out, it is observed. If there are no defects such as pinholes, bubbles, black spots, and no tinning, it is qualified; the workpiece to be plated is a surface-treated copper sheet (30mm×15mm×1.5 mm).
[0098] Table 1: Test parameters of tinning electrolyte in Examples 1-18 and Comparative Examples 1-16
[0099]
[0100]
[0101]
[0102]
[0103]
[0104] It can be seen from Example 1 and Examples 2-4 and Table 1 that the densifier prepared at a mass ratio of 1-(2-hydroxy-3-sulfopropyl)pyridine betaine salt, hydroxyethyl propargyl ether, and perfluorohexylethanol polyoxyethylene ether CAPSTONE FS-3100 of 15:7:3 is beneficial to improving the comprehensive patent of the tin plating layer, and the production cost is relatively low, which is convenient for large-scale market promotion.
[0105] It can be seen from Example 1 and Comparative Examples 1-3 and Table 1 that the addition of the compounded pH regulator and perfluorohexylethanol polyoxyethylene ether to the densifier can synergistically improve the quality of the tin-plated layer.
[0106] It can be seen from Example 1, Examples 5-6 and Comparative Examples 8-9 and Table 1 that the amount of the densifier added in the tin-plating electrolyte formula for improving the grain fineness of the tin-plating layer is preferably 3-8 g / L, preferably, the amount added is 5-6 g / L.
[0107] Combining Example 1, Examples 7-10 and Comparative Examples 4-5 and Table 1, it can be seen that the pH regulator in the densifier is composed of methanesulfonic acid, gluconic acid and pyrophosphoric acid in a mass ratio of (40-80):(10-20):(5-10), which can improve the quality of the tin-plated layer.
[0108] Combining Example 1 and Comparative Examples 6-7 with Table 1, it can be seen that the addition amount of perfluorohexylethanol polyoxyethylene ether CAPSTONE FS-3100 in the densifier is preferably controlled at 3-5wt%, which can ensure the quality and quality stability of the tin-plated layer.
[0109] Combining Example 1, Examples 11-18 and Comparative Examples 10-16 and Table 1, it can be seen that the electroplating parameters of the tin-plating electrolyte are as follows: the temperature of the environmentally friendly acidic tin-plating electrolyte is 45-50°C, the current density is controlled to be 3-5A / dm2, and the electroplating time is 3-6min, which can ensure the quality and quality stability of the tin-plated layer. Preferably, the electroplating parameters of the tin-plating electrolyte are as follows: the temperature of the environmentally friendly acidic tin-plating electrolyte is 50°C, the current density is controlled to be 3A / dm 2, the electroplating time is 4 minutes. The electrolyte formula is as follows: 48g / L stannous methanesulfonate, 80g / L methanesulfonic acid, 25g / L citric acid, 120g / L thiourea, 65g / L sodium hypophosphite, 8g / L 2-methyl-2,3-dihydrobenzaldehyde, 4g phthalimide, 6g / L alkylphenol polyoxyethylene ether OP-10, 4g / L PEG 300, 5g / L catechol, 5g / L hydroquinone, and 5g / L densifier for improving the grain fineness of the tin plating layer.
[0110] In summary, the tin-plated layer prepared by the densifier in the present invention combined with the tin-plating electrolyte formula provided by the present invention has finer grains, can improve the smoothness and uniformity of the tin-plated layer, and at the same time can give the tin-plated layer excellent solderability and solder resistance. The tin-plating process is stable, thereby achieving the stability of the tin-plating electrolyte, thereby improving the overall adhesion of the tin-plated layer.
[0111] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.
Claims
1. A densifier for improving the grain fineness of a tin-plated layer, characterized in that: It comprises a sustained-release membrane layer and a densifying agent composition coated in the sustained-release membrane layer, The densifier composition is composed of 14-16wt% of hydroxypropane sulfonic acid pyridinium salt, 5-8wt% of propynyl alcohol ethoxylate, 3-4wt% of perfluorohexylethanol polyoxyethylene ether, 14-16wt% of pH value regulator, and the balance is deionized water; The hydroxypropane sulfonic acid pyridinium salt is 1-(2-hydroxy-3-sulfopropyl) pyridinium salt, the propargyl alcohol ethoxylate is hydroxyethyl propargyl ether, and the perfluorohexylethanol polyoxyethylene ether is perfluorohexylethanol polyoxyethylene ether CAPSTONE FS-3100; The mass ratio of the 1-(2-hydroxy-3-sulfopropyl)pyridine betaine salt, hydroxyethyl propargyl ether, and perfluorohexylethanol polyoxyethylene ether CAPSTONE FS-3100 is (10-25):(5-15):(2-5); The pH value regulator is composed of methanesulfonic acid, gluconic acid and pyrophosphoric acid in a mass ratio of (40-80):(10-20):(5-10).
2. A densifier for improving the grain fineness of the tin-plated layer according to claim 1, characterized in that: The mass ratio of the 1-(2-hydroxy-3-sulfopropyl)pyridine betaine salt, hydroxyethyl propargyl ether, and perfluorohexylethanol polyoxyethylene ether CAPSTONE FS-3100 is 15:7:
3.
3. A densifier for improving the grain fineness of the tin-plated layer according to claim 1 or 2, characterized in that: The sustained-release film layer is a biaxially stretched PU film or a biaxially stretched PET film; the thickness of the sustained-release film layer is 50-100 microns; the sustained-release film layer is filled with a water-soluble filler, and the particle size of the water-soluble filler is 0.95-1.05 times the thickness of the sustained-release film layer.
4. A tin-plating electrolyte prepared by using the densifier for improving the grain fineness of the tin-plating layer according to any one of claims 1 to 3, characterized in that: The tin plating electrolyte comprises: 35-40 g / L of stannous methanesulfonate, 75-80 g / L of methanesulfonic acid, 25-30 g / L of citric acid, 100-120 g / L of thiourea, 60-80 g / L of sodium hypophosphite, 5-10 g / L of 2-methyl-2,3-dihydrobenzaldehyde, 1-5 g of phthalimide, 5-10 g / L of alkylphenol polyoxyethylene ether OP-10, 2-5 g / L of PEG300, 4-6 g / L of catechol, 4-6 g / L of hydroquinone and 3-8 g / L of a densifier for improving the grain fineness of the tin plating layer according to any one of claims 1 to 3.
5. The tin-plating electrolyte prepared by using a densifying agent for improving the grain fineness of the tin-plating layer according to claim 4, characterized in that: The pH value of the tin-plating electrolyte is 0.6-0.7; the electroplating parameters of the tin-plating electrolyte are as follows: the temperature of the environmentally friendly acidic tin-plating electrolyte is 45-50°C, and the current density is controlled to be 3-5A / dm 2 , the electroplating time is 3-6min.
6. A method for preparing a tin-plating electrolyte prepared by using a densifying agent for improving the grain fineness of the tin-plating layer according to claim 4 or 5, characterized in that: The following steps are involved: S1, preparation of a densifier for improving the grain fineness of the tin-plated layer; S1.1, 100 parts of PU resin or PET resin and 5-10 parts of inorganic filler with a water-soluble film attached to the surface are uniformly mixed, melt-extruded, cast, and biaxially stretched to obtain a sustained-release film layer with a thickness of 50-100 μm; S1.2, uniformly mixing accurately measured hydroxypropane sulfonic acid pyridinium salt, propargyl alcohol ethoxylate, perfluorohexylethanol polyoxyethylene ether, pH regulator, and deionized water to obtain a densifier composition; S1.3, using a laundry beads automatic packaging machine to coat the densifier composition prepared in S1.2 in the slow-release film layer in S1.1, so as to obtain a densifier with a particle size of 4-12 mm for improving the grain fineness of the tin-plated layer; S2, firstly, 100 parts of deionized water and 0.4-0.8 parts of triethylenetetraaminehexaacetic acid are mixed evenly and then placed in a reactor for boiling treatment for 5-15 minutes, and after boiling, the air in the reactor is replaced by nitrogen. After the boiling treatment is completed, the temperature is lowered to 0-20° C. and filtered to obtain a deionized water solvent; S3, put accurately measured stannous methanesulfonate, methanesulfonic acid, citric acid, thiourea, sodium hypophosphite, 2-methyl-2,3-dihydrobenzaldehyde, phthalimide, alkylphenol polyoxyethylene ether OP-10, PEG 300, catechol, hydroquinone, and the densifier used to improve the grain fineness of the tin plating layer in S1 into a reactor and stir them evenly with the impurity-removed water solvent obtained in S2, then add methanesulfonic acid dropwise to adjust the pH value of the system to 0.6-0.7, and a finished tin plating electrolyte can be obtained.
Citation Information
Patent Citations
Multi-functional half-white brightness tin-plated additive
CN104562100A
Degradable environment-friendly tin plating electrolyte
CN105274586A